Uji Aktivitas Antidiare Infusa Kulit Buah Delima Putih (Punica granatum L.) pada Mencit Jantan Swiss Webster dengan Metode Oleum Ricini - Nur Rahayuningsih; Siti Nuurul Hidayah Assyifa; Ira Rahmiyani (Fakultas Farmasi Universitas Pancasila, 2021)
Diarrhea is a condition in which a person defecates with a soft or liquid consistency, which can evenbe water. Diarrhea can be treated with drugs derived from plants, one of which is white pomegranate skin. Theskin of white pomegranate (Punica granatum L.) is thought to have anti-diarrheal activity because it has fl avonoidsand tannins. This study aims to determine the activity and optimal dose of pomegranate skin infusion.Mice were grouped into 5 groups: negative control (Na CMC 0.5%), positive control (Loperamid HCl), andpomegranate peel infusion test group with a dose of 8 mg / 20 g mice BW, 16 mg / 20 g weight mice and 32 mg./ 20 gr BB mouse. Mice induced diarrhea with Oleum ricini, 30 minutes later the mice were given a test preparation.The onset of diarrhea, stool consistency, diarrhea frequency, duration of diarrhea and stool weight weremeasured every 30 minutes for 6 hours. The results showed that the fi rst dose (8 mg / 20 gr BW of mice) wasthe optimal dose for the initial parameters of diarrhea and fecal weight, which means that there was a signifi cantdiff erence with negative control and positive control (<0.05). The parameters of stool consistency, frequency ofdiarrhea and duration of occurrence of diarrhea showed no signifi cant diff erence between groups of 8 mg / 20 gmice BW, 16 mg / 20 g mice BW and 32 mg / 20 g mice BW, negative control and positive control (p> 0, 05).